Metode Pendidikan Profetik dalam Al-Qur’an: Kajian Ayat-ayat Kisah Nabi Ibrahim AS - Syarif H, Sarto Al; Manshur, Fadlil Munawwar (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2017)
This article on the method of prophetic education in the Qur'an shows that the methods of prophetic education in the verses of Ibrahim's story are intuitive methods, rational methods, exemplary methods, phasing methods (stages of recitations, ta'lim stages, tazkiyyah stages, and wisdom stage), dialogical method, method of ibrah, mau'izah, advice, method of demonstration, method of punishment and reward, method of prayer, assignment method, and wasiat method. All of the educational methods found in the verses of Prophet Ibrahim's story are relevant to current Islamic education.